When Do Observers Deprioritize Due Process for the Perpetrator and Prioritize Safety for the Victim in Response to Information-Poor Allegations of Harm?. (February 2023) - Graso, Maja; Aquino, Karl; Chen, Fan Xuan; Camps, Jeroen; Strah, Nicole; van den Bos, Kees
We examined how observers assess information-poor allegations of harm (e.g., "my word against yours" cases), in which the outcomes of procedurally fair investigations may favor the alleged perpetrator because the evidentiary standards are unmet. Yet this lack of evidence does not mean no harm occurred, and some observers may be charged with deciding whether the allegation is actionable within a collective. On the basis of theories of moral typecasting, procedural justice, and uncertainty management, we hypothesized that observers would be more likely to prioritize the victim's safety (vs. to prioritize due process for the perpetrator) and view the allegation as actionable when the victim-alleged perpetrator dyad members exhibit features that align with stereotypes of victims and perpetrators. We supported our hypothesis with four studies using various contexts, sources of perceived prototypicality, due-process prioritization, and samples (students from New Zealand, N s = 137 and 114; Mechanical Turk workers from the United States; N s = 260 and 336).